Inexpensive termite control - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Termites can be controlled without resorting to costly imported chemicals. Field trials have shown that preparations using locally available materials have been effective. In India, for example, Gondal fluid made from 100g gum, 200g asafoetida,...